Interferon-α inhibits CD4 T cell responses to interleukin-7 and interleukin-2 and selectively interferes with Akt signaling. Issue 6 (17th March 2015) - Nguyen, Thao P; Bazdar, Doug A; Mudd, Joseph C; Lederman, Michael M; Harding, Clifford V; Hardy, Gareth A; Sieg, Scott F
Abstract : IFN- α can selectively inhibit cytokine-induced P-Akt as a potential mechanism to disrupt homeostasis of T lymphocytes. Abstract: Persistent type I IFN production occurs during chronic viral infections, such as HIV disease. As type I IFNs have antiproliferative activity, it is possible that chronic exposure to these cytokines could adversely affect T cell homeostasis. We investigated the capacity of IFN- α to impair T cell proliferation induced by the homeostatic cytokine, IL-7, or another common γ -chain cytokine, IL-2, in cells from healthy human donors. We found that IL-7- or IL-2-induced proliferation of CD4 + T cells was partially inhibited in the presence of IFN- α . The CD4 + T cells that were exposed to IFN- α also displayed attenuated induction of IL-2 and CD40L following TCR stimulation. Analyses of signaling pathways indicated that IL-7 and IL-2 induced a delayed and sustained P-Akt signal that lasted for several days and was partially inhibited by IFN- α . In contrast, IL-7-induced P-STAT5 was not affected by IFN- α . Furthermore, IFN- α had no detectable effect on P-Akt that was induced by the chemokine SDF-1. Both inhibitors of P-Akt and P-STAT5 blocked IL-7-induced T cell proliferation, confirming that both signaling pathways are important for IL-7-induced T cell proliferation. These results demonstrate that IFN- α can selectively inhibit cytokine-induced P-Akt as a potential mechanism to disrupt homeostasis of T lymphocytes.